A Primeira Guerra Mundial nas escolas: currículos e livros didáticos - Francisco Eduardo Alves de Almeida; Carolina Mary Medeiros (Navigator)
In the year 1914, World War I began. A hundred years ago, Brazil participated in this great event that would undoubtedly change world history. Despite the great relevance, little has been studied on the subject, mainly, the participation of Brazil in this process. If in historiography the theme is rare, so does history teaching. In this article, we analyze two didactic books used in the Colégio Pedro II, as well as the program of the discipline of History of the college in relation to the theme. We verified that in the textbooks, or in the program, the participation of Brazil in World War I and its consequences is a theme now silenced, now analyzed in a restricted way.